DECOMPOSITION OF THE AIR ROUTES NETWORK - Юн, Г. М.; Марінцева, К. В. (Science-based technologies, 2014)
The concept of route network decomposition that includes major airports with high level of passenger traffics is suggested. The effect of air routes network decomposition is considered from the viewpoint of passengers, airlines and aircraft industries. It is determined that the impact of the routes network decomposition concept can be measured by passenger-kilometres decrease, time-saving and comfort improvement. The mathematical model of passenger traffic on the existing and extended network, taking into account existing and updated aircraft park, is developed .The gain of airlines is that implementation of the concept gives the opportunity to maximize profit and the resetting percentage of the invested capital. Hub airports gain is their unloading. And as a result of reduction of the delay is not excluded the possibility to return part of the passenger traffic on feeder routes. Aircraft manufacturing company due to the new approach to the structure of the routes network should work on a large number of types and sizes of aircraft that meet the needs arising on the routes with different density of traffic.